EFFECT OF TEACHER'S LIKABILITY ON STUDENT'S ATTITUDE TOWARDS PHYSICS: AN EMPIRICAL STUDY OF SECONDARY SCHOOL STUDENTS IN ENUGU STATE, NIGERIA - Ede, Margaret N. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
Physics is one of the most important scientific disciplines taught in Nigeria's secondary school curriculum. Students' poor performance in physics has become a growing concern. The purpose of this study was to see if teacher likability could have an impact on students' views about physics. A cross-sectional survey was used in this investigation. The survey's participants are secondary school students from Enugu State, Nigeria. Male and female senior secondary school students took part in the study. The majority of them came from science class. A total of 139 students were involved in the research. A Teacher's Likability Scale and the Physics Attitude Scale (PAS) were used to collect data. The results revealed that the majority of respondents had a negative attitude toward subject (M = 0.87, SD = 0.35), while only a handful (M = 0.18, SD = 0.39) had a favorable attitude. A linear regression model was used to test the main hypothesis. The findings revealed that teachers' likability statistically significantly influenced students' attitudes toward physics F(1,137), 40.16 p.05. According to the findings, a teacher's likability strongly predicts students' attitudes about physics. As a result, it is suggested that teachers act more as facilitators than harsh educators.